SOME ASPECTS OF COLLOCATION IN KURDISH - MOHAMMED, DR. ABDULLAH AZEEZ (Journal of Duhok University, 2019)
This study deals with some aspect of the phenomenon of collocation in Kurdish which is one of the fields of semantics. This field of study is very wide and comprehensiwe. It is confused with semantic fields, metaphor, polysemy, hyponymy and memronymy. The researcher has divided collocation into basic meaning and secondary meaning. In this study, only the basic meaning of collocation has been dealt with in order to conduct on independent study of collocation and enriching it from various prespechres by allocating and identifying some aspects for it such as sound meaning, social coexistence, movements, prophets and caliphs features, foods, fruits and some other short phenomena. It is to be noted that this study has an effective role in enriching the Kurdish language and lexicology.